Prevalence of health risk behaviours among the school going adolescents of Gwalior township - Swami, Piyush Datt; Sukla, Pradeep; Kumar, Sanjeev (International Journal Of Community Medicine And Public Health, 2019)
Background: The high-risk behaviors are defined as behaviors which threat health and well-being of adolescences, youth and other society’s members. Habits and behaviour that acquired in adolescent have influence in adulthood as well. Health risk behaviors such as alcohol use, smoking, substance use, unsafe driving, unintentional injuries and violence and sexual risk behaviors among adolescents is widely prevalent. Adolescent have tendency to experiments new things, they want to explore new things because of this they have risk taking behavior, this nature is also due to hormonal surge and emotional predominance. The aim and objectives of this study was to estimate the prevalence of health risk behaviors and on the basis of key findings suggest recommendations. Methods: This study is based on self-reported experiences of health risk behavior by school going adolescents. Adolescents are selected by the simple random sampling, and data is collected by the semi-structured, self-administered questionnaire. Results: 26% adolescents experience road traffic accident, 4.5% experience assault. 11% were used to smoke, 9% nonsmoking products, 2.67% uses alcohol some time in their life. 9% adolescents experience symptoms of RTI. Conclusions: Adolescent stage is a period of various changes so they need proper care, support and counseling to cope with this transition phase.